Factors, trends, and long-term outcomes for stroke patients returning to work: The South London Stroke Register. Issue 7 (October 2019) - Sen, Arup; Bisquera, Alessandra; Wang, Yanzhong; McKevitt, Christopher J; Rudd, Anthony G; Wolfe, Charles D; Bhalla, Ajay
Background and purpose: There is limited information on factors, trends, and outcomes in return to work at different time-points post-stroke; this study aims to identify these in a multi-ethnic urban population. Methods: Patterns of return to work were identified in individuals in paid work prior to first-ever stroke in the population-based South London Stroke Register (SLSR) between 1995 and 2014. Multivariable logistic regression examined associations between patient characteristics and return to work at 1 year (1 y), 5 years (5 y) and 10 years (10 y) post-stroke. Results: Among 5609 patients, 940 (17%) were working prior to their stroke, of whom 177 (19%) were working 3 months post-stroke, declining to 172 (18%) at 1 y, 113 (12%) at 5 y, and 27 (3%) at 10 y. Factors associated with return to work within 1 y, after logistic regression, included functional independence (BI ≥ 19; p < 0.01) and shorter length of stay ( p < 0.05). Younger age ( p < 0.01) was associated with return to work at 5 y and 10 y post-stroke. Non-manual occupation ( p < 0.05) was associated with return to work at 10 y post-stroke. Return to work within 1 y increased the likelihood of working at 5 y (OR: 13.68; 95% CI 5.03–37.24) and 10 y (9.07; 2.07–39.8). Of those who were independent at follow-up (BI ≥ 19), 48% were working at 1 y, 42% at 5 y, and 28% at 10 y. Lower rates of anxiety and depression and higher self-rated health were associated with return to work at 1 y ( p < 0.01). Conclusion: Although functionally independent stroke survivors are more likely to return to work long-term, a large proportion do not return to work despite functional independence. Return to work post-stroke is associated with improved long-term psychological outcomes and quality of life.